Psihiatrična obravnava otrok in mladostnikov s kronično telesno boleznijo - Drobnič Radobuljac, Maja (Zdravniški vestnik, 2014)
Children with chronic illness and their families are at a higher risk for the development of mental disorders, and these may negatively affect the psychosocial development of children at different developmental stages. Mental disorders in children or their families affect the compliance in the treatment of chronic somatic illness and consequently cause higher disability. The present article describes various ways in which a chronic illness can influence mental states of children and their families, as well as the role of family member's mental disorder in treatment compliance. It also describes the role of the child and adolescent psychiatrist in the management of these children and their families.
Keywords: children and adolescents; chronic condition; chronic illmess; kronična bolezen; otroci in mladostniki; psihične težave; psychological problems